Perbedaan Kadar Kolestrol Total Pada Pengonsumsi Kopi dan Bukan Pengonsumsi Kopi Di Banjar Juwet Abiansemal - Ni Kadek ary Astuti; Putu Ayu Parwati; Anak Agung Ayu Eka Cahyani (Journal of Medical Laboratory Research, 2025)
Coffee contains bioactive compounds such as caffeine, cafestol, and kahweol that can influene lipid metabolism. Consumption of unfiltered coffee (boiled coffee) has the potential to increase cholesterol levels. This study aimed to determine the difference in total cholesterol levels between coffee consumers in Banjar Juwr, Abiansemal. The research employed a quantitative comparative method with an observational design. A total of 70 male respondents age 20-50 years (35 coffee consumers and 35 non-consumers) were selected using purposive sampling. Total cholesterol levels were measured using the test strip method (Easy Touch GCU). Data were analyzed using the Independent Sample T-Test. The mean total cholesterol levels of coffee consumers was 170.49 mg/dL, while that of non-consumers was 178.80 mg/dL. Statistical analysis showed p=0.103 (p>0.05), indicating no significant difference between the two groups. Conclusion Black coffee consumption in Banjar Juwet was not proven to significantly affect total cholesterol levels. Other factors such as dietary patterns, phhysical activity, and health history are presumed to play a greater role.